Knowledge of School Residents' on Self-Evacuation of Natural Disaster Victims at SMP Negeri 1 Botupingge - Ilato, Khairurrijal Irsha; Yusuf, Zuhriana K; Abdul, Romy; Pateda, Sri Manovita; Paramata, Nanang Roswita (Jambura Medical and Health Science Journal, 2025)
Introduction: Natural disasters can cause significant losses to life, the environment, and the economy. In the past decade, Gorontalo Province recorded 169 disasters. Schools play a crucial role in disaster management through risk education, evacuation drills, and community protection. This study assesses the knowledge of self-evacuation procedures among school residents at SMP 1 Botupingge. The findings will help develop better educational programs to enhance school and community disaster preparedness.Method: This quantitative descriptive study involved 313 individuals, with final sample size 63 selected through accidental sampling. Data were collected using a validated questionnaire and analyzed with univariate tests.Results: Most respondents had "good" category knowledge of self-evacuation (55.6%), followed by "sufficient" category (41.3%) and "insufficient" category (3.1%).Conclusion: The majority of SMP Negeri 1 Botupingge residents mostly demonstrate good self-evacuation knowledge. Regular simulations and training are recommended to strengthen disaster preparedness.Key words: Disaster planning, knowledge, natural disasters,self evacuation